Intuitive Face Judgments Rely on Holistic Eye Movement Pattern - Mega, Laura F.; Volz, Kirsten G. (Frontiers in Psychology, 2017)
Nonverbal signals such as facial expressions are of paramount importance for social encounters. Their perception predominantly occurs without conscious awareness and is effortlessly integrated into social interactions. In other words, face perception is intuitive. Contrary to classical intuition tasks, this work investigates intuitive processes in the realm of every-day type social judgments. Two differently instructed groups of participants judged the authenticity of emotional facial expressions, while their eye movements were recorded: an ‘intuitive group’, instructed to rely on their “gut feeling” for the authenticity judgments, and a ‘deliberative group’, instructed to make their judgments after careful analysis of the face. Pixel-wise statistical maps of the resulting eye movements revealed a differential viewing pattern, wherein the intuitive judgments relied on fewer, longer and more centrally located fixations. These markers have been associated with a global/holistic viewing strategy. The holistic pattern of intuitive face judgments is in line with evidence showing that intuition is related to processing the “gestalt” of an object, rather than focusing on details. Our work thereby provides further evidence that intuitive processes are characterized by holistic perception, in an understudied and real world domain of intuition research.